The Effectiveness Of The Method of GI With Electronic Workbench Study To Improve Activities and Results Student - Devit Etika Sari (STAI Miftahul Ula Nganjuk, 2018)
Effectiveness of Cooperative Learning Model Gi(Group Investigation)with EWB(Electronic Work bench)in increasing student activity and learning outcomes is research that aims to know the management of learning, student activities and student learning outcomes during the learning process takes place in class X TAV 1 in SMK Negeri 1 Lengkong. The results showed that the activity of students in each round encounter Improvement. Activities include learning students' visual activities, writing activities, drawing activities, oral activities, bike activities and emotional activities. Averages of student activity that arise during the learning process is Visual Activities in the 1st round by 59.7% in the 2nd round by 76.9% and amounted to 87.6% 3. Writing Activities in rounds 1 53.7% in the 2nd round by 72.7% in the 3rd round of 86.1%. Drawing activities in round 1 of 0% in the 2nd round by 84.7% and amounted to 95.1% 3. Oral activities in the 1st round of 36.25% in the 2nd round 80.6% and amounted to 86.2% 3. Motor activitiesin the 1st round by 53.5% in the second round of 80.6% in the third round of 85.9%. Emotional activities in the 1st round by 66.7% in the 2nd round sebesar80,6 3% and amounted to 91.7%. Assessment of student learning outcomes in the study include tests of performance and portfolio assessment using Cooperative Learning GI(Group Investigation)With EWB(Electronic Work bench)proven effective in increasing student learning outcomes evidenced by the level of mastery learning students is increasing at each revolution is round 1sebesar 69.4% .In second round of 86.1% and by 94.4% to 3.